2000
DOI: 10.1046/j.1365-2648.2000.01492.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematized HIV/AIDS education for student nurses at the University of Ibadan, Nigeria: impact on knowledge, attitudes and compliance with universal precautions

Abstract: This paper reports the findings of a study which examines changes in a group of Bachelor of Science (BSc) nursing students' perceptions, knowledge of and attitudes towards human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), accruing from attempts at a systematized education for the cohort. Based upon a 3-month study of 141 registered nurses enrolled in a BSc nursing programme at the University of Ibadan, Nigeria, it investigates alterations in knowledge and attitudes resulting from inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 11 publications
4
60
1
1
Order By: Relevance
“…The result of this study corroborates the results of previous studies (e.g., Mohsen, 1998;Uwakwe, 2000). Thus, we need to combine several education methods to achieve a positive effect on nurses' knowledge and attitudes.…”
Section: Discussionsupporting
confidence: 94%
“…The result of this study corroborates the results of previous studies (e.g., Mohsen, 1998;Uwakwe, 2000). Thus, we need to combine several education methods to achieve a positive effect on nurses' knowledge and attitudes.…”
Section: Discussionsupporting
confidence: 94%
“…The study concluded that it is very important for education to be incorporated within undergraduate and in-service training programs for nurses about Universal Precautions. (9) A study conducted by JB Suchitra and N Lakshmi Devi (8) showed the similar findings. Our study also showed statistically significant association between formal education received on hand hygiene and knowledge on hand hygiene.…”
Section: Discussionsupporting
confidence: 68%
“…Measures to ensure universal precautions in health care settings may not be readily available to Ugandan health care providers, which may explain a greater sense of fear of providing direct care (Mungherera et al, 1997). Fear of contagion from patient care activities was also a common result within the literature (Mbanya et al, 2001;Mungherera et al, 1997;Uwakwe, 2000). Not only has fear been described in relation to knowledge and attitude scores, researchers have reported that it has an impact on patient care.…”
Section: Discussionmentioning
confidence: 79%